2022
DOI: 10.1186/s42358-022-00271-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the Brazilian online version of the Fibromyalgia Rapid Screening Tool (FiRST)

Abstract: Objective The Fibromyalgia Rapid Screening Tool (FiRST) was developed to screen people with chronic pain for Fibromyalgia (FM), especially in primary health care settings. This study aimed to translate the FiRST into Brazilian Portuguese and evaluate its measurement properties for an online application. Methods After the process of translation and backtranslation, the FiRST was applied online in 483 adults with chronic pain (FM group n = 395; Chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Originally FiRST was developed in French and English and has been translated according to the MAPI Research Trust website into Arabic, German, Greek, Portuguese, Spanish, Turkish, and Ukrainian languages [31]. The linguistic validation (with results available in English) was performed for Arabic [15], Greek [17], Portuguese [16], Spanish [13,14] and Turkish [18] versions. Our Polish version of FiRST compared to other language versions showed slightly lower internal consistency (Cronbach's α = 0.644 vs 0.7-0.787) [13,15,17] and comparable test-retest reliability (ρ = 0.75 vs 0.76-0.875) [15,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally FiRST was developed in French and English and has been translated according to the MAPI Research Trust website into Arabic, German, Greek, Portuguese, Spanish, Turkish, and Ukrainian languages [31]. The linguistic validation (with results available in English) was performed for Arabic [15], Greek [17], Portuguese [16], Spanish [13,14] and Turkish [18] versions. Our Polish version of FiRST compared to other language versions showed slightly lower internal consistency (Cronbach's α = 0.644 vs 0.7-0.787) [13,15,17] and comparable test-retest reliability (ρ = 0.75 vs 0.76-0.875) [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the development study, FiRST showed a sensitivity of 90.5% and a specificity of 85.7% (AUC = 0.93) in diagnosing FM (according to 1990 ACR criteria), while also showing good consistency of the test over time (ICC = 0.87). As of today, FiRST has been translated and validated into several languages, showing good psychometric properties [13][14][15][16][17][18]. However, there is no Polish language version of FiRST.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the French and the English versions of FiRST [ 22 ], FiRST has been translated according to MAPI Research Trust website into Dutch, Belgium, German, Greek, Italian, Portuguese, Russian, Spanish, Turkish, and Ukrainian languages [ 23 ]. The linguistic validation was not applied to all translations [ 23 ], and limited to the Spanish [ 45 ], Greek [ 46 ], Brazilian [ 47 ], and Turkish [ 48 ] versions. The Arabic translation and validation of the FiRST have not been investigated previously.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our findings with other validated Spanish [ 45 ], Greek [ 46 ], Brazilian [ 47 ], and Turkish [ 48 ] versions of FiRST. In the Spanish study conducted by Torres and colleagues [ 45 ], participants with suspected FM ( n = 172) were included in the study and were compared to a group of controls (non-FM = 85).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation